TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDESA) BULUSARI KECAMATAN KALIPURO KABUPATEN BANYUWANGI TAHUN 2020 - Himawan Pradipta; Achmad; Siti Rohmah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
The village government has a strategic role in national development. The success of the village government in realizing the program will have an indirect impact on the central government program. One of the supporting factors that influence the implementation of village government programs, namely the financial management of the Village Budget. So to ensure the implementation of public services, the government issues regulations and laws governing the management of these village funds. This is aimed at realizing good village governance. The Bulusari village government is one of the villages that has implemented good financial management. The management of the Bulusari Village Budget consists of planning, implementation, administration, reporting, and accountability activities in accordance with the provisions stipulated in the Regulation of the Minister of Home Affairs. In addition, the management of the Bulusari APBDesa has implemented the principles of transparency and public accountability